Learning by doing in market reform: Lessons from a regional bond fund - Guonan Ma; Eli M. Remolona (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2006)
Local currency bond markets in East Asia and the Pacific have grown impressively since the 1997 Asian crisis, but policy authorities in the region realize they still have some work to do to allow the markets to realise their true potential. Hence, there have been a variety of regional initiatives to develop these markets. One of these initiatives is the Asian Bond Fund II, which was established by 11 central banks in East Asia and the Pacific in 2005. In creating a regional index bond fund and eight single-market funds, the central banks worked together to identify and come up with ways to reduce market impediments in eight local currency bond markets. Moreover, they built into the regional fund's structure an incentive mechanism for reducing impediments further.
Keywords: E44; G15; G18; O16; 330